Differences in delivery of respiratory treatments by on-call physiotherapists in mechanically ventilated children: a randomised crossover trial. Issue 4 (December 2015) - Shannon, Harriet; Stocks, Janet; Gregson, Rachael K.; Hines, Sarah; Peters, Mark J.; Main, Eleanor
Abstract: Objectives: To investigate differences, if any, in the delivery of respiratory treatments to mechanically ventilated children between non-respiratory on-call physiotherapists and specialist respiratory physiotherapists. Setting: Paediatric, tertiary care hospital in the United Kingdom. Participants: 93 children (aged between 3 days and 16 years), and 22 physiotherapists (10 specialist respiratory physiotherapists) were recruited to the study. Interventions: Recruited children received two physiotherapy treatments during a single day, one delivered by a non-respiratory physiotherapist, the other by a specialist respiratory physiotherapist in a randomised order. Selection, delivery and effects of techniques were recorded for each treatment. Outcome measures: Primary outcomes were selection and application of treatment components. Secondary outcomes included respiratory effects (in terms of changes in flow, volume and pressure) of selected treatment components. Results: Both non-respiratory on-call physiotherapists and specialist respiratory physiotherapists used combinations of saline instillation, manual lung inflations, chest wall vibrations and endotracheal suction during treatments. However specialist respiratory physiotherapists used combinations of chest wall vibrations with suction, and recruitment manoeuvres, significantly more frequently than non-respiratory on-call physiotherapists (92% vs 52%, and 87% vs 46% of treatments respectively, P < 0.001). Chest wall vibrations delivered by non-respiratory on-call physiotherapists were 15% less effective at increasing peak expiratory flow. Conclusion: Clinically important differences between non-respiratory and specialist respiratory physiotherapists' treatment outcomes may be related to differences in the selection and application of techniques. This suggests an important training need for non-respiratory on-call physiotherapists, particularly in the effective delivery of physiotherapy techniques. Trial registration: Clinicaltrials.govNCT01999426 .